The Effectiveness of Cooperative Learning Model and Interpersonal Intelligence on Motivation of Primary Teacher Education Students - Arihi, La Ode Safiun; Sulfadli, Sulfadli; Arisanti, Wa Ode Lidya; Uge, Sarnely; Hikmawati, Hikmawati (JTP - Jurnal Teknologi Pendidikan, 2024)
The learning process greatly influences student activity and behavior, causing students to be more active in the learning process when learning is designed with a good teaching style. Students are expected to always be active and have intelligence that will be a provision when they become educators, but in fact, in the field, many students always complain about the indoor lecture process and that interpersonal intelligence is not used enough by students. This research aims to analyze whether the application of the two stay two stray learning model can improve PKN students' understanding of concepts. The method used in this research is a quantitative survey method. The population in this study was 98 students and 10 people with PGSD doses. Data collection uses observation and questionnaires with data analysis methods including validity and reliability tests, normality tests, linearity tests. The results of the research show that the significance value for the influence of X1 and It is hoped that this will serve as material for consideration in order to increase students' motivation and interpersonal intelligence and also as a suggestion for future researchers so that they can carry out research by encouraging students' interpersonal intelligence to be better and developing the learning process